The relation of aortic dimensions and age-anthropometric data in women with Marfan syndrome - Pidvalna , U.Ye.; Beshley , D.M.; Mateshuk-Vatseba , L.R. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. The high level of morbidity and mortality from damage to the cardiovascular system remains an urgent problem of modern medicine. Women with Marfan syndrome suffer from acute aortic syndrome. Timely diagnosis and analysis of the aortic size are key in planning cardiac surgery and preventing fatal outcomes. Objective. To analyze the dimensions of the ascending aorta by computer tomography in women with Marfan syndrome and establish the correlation of the aortic diameter with age-anthropometric parameters. Methods. ECG-synchronized contrast-enhanced computed tomography, anthropometric, morphometric, mathematical and statistical methods. Materials were DICOM files of female patients with Marfan syndrome. Results. The study included women with Marfan syndrome, n=6, average age 44.33±13.08 years, average body length 1.67±0.05 m, average body weight 71.00±17.84, average mass index of the body 25.62±7.05 kg/m², the average value of the surface area of the body 1.80±0.22 m2. In women with Marfan syndrome, a direct strong correlation was established between the body mass index and the diameter of the aorta at the level of the aortic sinuses (sinus of Valsalva) (ρ= +0.82, p=0.044). This relationship is digitally confirmed by the method of linear regression (R=0.98, p<0.001). A direct strong correlation was established between the diameter of the aorta at the level of the sinotubular junction and the body weight, body surface area (ρ= +0.84, р=0.039) and a multiple correlation-regression relationship between the body mass index, body surface area and the aortic diameter at the level of the aortic sinuses (R= +0.97, p=0.04). Conclusion. In women with Marfan syndrome, a relationship was established between body mass index and aortic diameter at the level of the aortic sinuses, as well as correlation between body mass index, body surface area and the aortic diameter at the level of the sinotubular junction and aortic sinuses. The results emphasize the need for regular diagnostic monitoring of the size of the aorta in women with Marfan syndrome, taking into account age and anthropometric parameters.